Some multidimensional fixed point theorems for nonlinear contractions in C-distance spaces with applications - Maliha Rashid; Naeem Saleem; Rabia Bibi; Reny George (Journal of Inequalities and Applications, 2024)
Abstract In this manuscript, we use the concept of multidimensional fixed point in a generalized space, namely, C-distance space with some nonlinear contraction conditions, such as Jaggi- and Dass-Gupta-type contractions. We provide results with a Jaggi-type hybrid contraction for the mentioned space. Moreover, we use control functions to get the desired results. After each theorem, we compare our results with previous ones to show that they are generalized. We provide examples to support our results. An application is also performed to solve the system of integral equations.